ANALISIS PERBANDINGAN MODEL PREDIKSI FINANCIAL DISTRESS PADA SUB SEKTOR PERKEBUNAN - Fanny, Triesie Avrilia; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out whether there is prediction model difference of Altman, Springate, and Zmijewskiin predicting the condition of financial distress on plantation companies in 2012-2014 periods. And to find outwhich model is the most accurate in predicting the condition of financial distress of plantation companies in 2012-2014 periods. The samples collection has been carrie out by using purposive sampling technique. The independentvariables in this research is Altman, Springate, and Zmijewski model whereas the dependent variable dependent inthis research is financial distress. The data analysis has been carried out by using one way ANOVA difference testand accuracy level. Based on the result of the research it can be concluded that the existence of the prediction modeldifference of Altman, Springate, and Zmijewski in predicting the condition of financial distress on plantationcompanies in 2012-2014 periods which are listed in Indonesia Stock Exchange. The result of the research has foundthat Zmijewski has accuracy level 82% whereas Altman model has accuracy level 55% and Springate has accuracylevel 45%. It shows that Zmijewski model is the most accurate model in predicting the condition of financial distresson plantation companies which are listed in Indonesia Stock ExchangeKeywords: Financial distress, altman, springate, zmijewski